OBSTACLES TO UTILIZATION OF DENTAL SERVICES IN KARACHI, PAKISTAN - Azam Muhammad Aliuddin (Army Medical College Rawalpindi, 2021)
Objective: To determine the different views of the people, regarding dental health, based on gender and level of education.